Fruit development of the diploid kiwifruit, Actinidia chinensis 'Hort16A' - Richardson Annette C; Boldingh Helen L; McAtee Peter A; Gunaseelan Kularajathevan; Luo Zhiwei; Atkinson Ross G; David Karine M; Burdon Jeremy N; Schaffer Robert J (BMC Plant Biology, 2011)
Abstract Background With the advent of high throughput genomic tools, it is now possible to undertake detailed molecular studies of individual species outside traditional model organisms. Combined with a good understanding of physiological processes, these tools allow researchers to explore natural diversity, giving a better understanding of biological mechanisms. Here a detailed study of fruit development from anthesis through to fruit senescence is presented for a non-model organism, kiwifruit, Actinidia chinensis ('Hort16A'). Results Consistent with previous studies, it was found that many aspects of fruit morphology, growth and development are similar to those of the model fruit tomato, except for a striking difference in fruit ripening progression. The early stages of fruit ripening occur as the fruit is still growing, and many ripening events are not associated with autocatalytic ethylene production (historically associated with respiratory climacteric). Autocatalytic ethylene is produced late in the ripening process as the fruit begins to senesce. Conclusion By aligning A. chinensis fruit development to a phenological scale, this study provides a reference framework for subsequent physiological and genomic studies, and will allow cross comparison across fruit species, leading to a greater understanding of the diversity of fruits found across the plant kingdom.